Well-being in the information society : fighting inequalities : 7th International Conference, WIS 2018, Turku, Finland, August 27-29, 2018, Proceedings /: fighting inequalities : 7th International Conference, WIS 2018, Turku, Finland, August 27-29, 2018, Proceedings. (2018) - Unknown
No abstract available